2007
DOI: 10.1152/japplphysiol.01183.2006
|View full text |Cite
|
Sign up to set email alerts
|

Aging, exercise, and endothelial progenitor cell clonogenic and migratory capacity in men

Abstract: Numerical and functional impairment of circulating endothelial progenitor cells (EPCs) is thought to contribute to vascular aging and the associated increase in cardiovascular risk. We tested the following hypotheses: 1) EPC clonogenic and migratory capacity decrease progressively with age in healthy, sedentary adult men; and 2) regular aerobic exercise will improve EPC clonogenic and migratory capacity in previously sedentary middle-aged and older men. Peripheral blood samples were collected from 46 healthy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
3
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(118 citation statements)
references
References 49 publications
9
101
3
4
Order By: Relevance
“…In contrast to CD31 ϩ T-cell number, migratory capacity declined precipitously from the young to the middleaged men and was not different between the middle-aged and older men. This temporal pattern is similar to that previously reported for endothelial progenitor cells (19), supporting the notion that CD31 ϩ T cells comprise part of the circulating vascular progenitor milieu (20). Reduced migratory capacity of circulating CD31 ϩ T cells with age may seriously compromise vascular repair processes and contribute to poor clinical outcomes (13).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In contrast to CD31 ϩ T-cell number, migratory capacity declined precipitously from the young to the middleaged men and was not different between the middle-aged and older men. This temporal pattern is similar to that previously reported for endothelial progenitor cells (19), supporting the notion that CD31 ϩ T cells comprise part of the circulating vascular progenitor milieu (20). Reduced migratory capacity of circulating CD31 ϩ T cells with age may seriously compromise vascular repair processes and contribute to poor clinical outcomes (13).…”
Section: Discussionsupporting
confidence: 86%
“…The migratory capacity of CD31 ϩ T cells was assessed using a modified Boyden chamber technique, as previously described by our laboratory (19). Briefly, 4 ϫ 10 5 cells were resuspended in culture medium consisting of RPMI 1640 (CellGro; Mediatech, Manassas, VA), penicillin (100 U/ml), and streptomycin (100 g/ml) and then placed in the upper buffer chamber of a 24-well modified Boyden chamber coated with fibronectin (FluoroBok; BD Biosciences).…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of NO for the exercise-induced release of EPCs was supported by the analysis of eNOS knockout mice. These results could be confirmed by several other groups investigating patients with coronary artery disease (74), peripheral vascular occlusive disease (9), chronic heart failure (75), hemodialysis (76), or even health controls (77,78). Even in school children, a recent study from our group confirmed the impact of exercise on EPCs (79).…”
Section: Physical Exercisesupporting
confidence: 86%
“…Recent studies evidenced aerobic ET as responsible for promoting higher release and improving the bone-marrow derived EPC functional properties both in humans and animals, which contributes to the improvement of the endothelial function, angiogenesis and consequently, maintenance of cardiovascular homeostasis [13][14][15][16][17][18][19] . Although the ET effect on the EPC parameters has been evidenced, studies with alteration in the ET volume on the EPC and the capillarization have not been found yet.…”
Section: Introductionmentioning
confidence: 99%